Legal Study on the Limitation of Wills for Legitimate Interests Seen from the Civil Code and the Compilation of Islamic Law - Difanri Ramadhan Siregar, Muhammad; Trisna Dewi , Ayu; Safnul, Dody (Tasyri' : Journal of Islamic Law, 2026)
A will is an instrument of inheritance law that grants the testator the authority to determine the distribution of their estate; however, such authority is limited by the rights of certain heirs known as legitimaries. In the Indonesian legal system, restrictions on wills are regulated in the Civil Code (KUH Perdata) through the concept of legitieme portie and in the Compilation of Islamic Law (KHI) through a limitation of a maximum of one-third of the estate. This article aims to examine the legal position of legitimaries, the forms of restrictions on wills, and the concept of justice in limiting wills under the Civil Code and the Compilation of Islamic Law. This study employs a normative juridical method with statutory and conceptual approaches. The findings indicate that restrictions on wills function as legal protection for legitimaries to ensure the minimum rights of heirs and to maintain a balance between testamentary freedom and justice in inheritance law.